2022
DOI: 10.1596/978-1-4648-1865-3
|View full text |Cite
|
Sign up to set email alerts
|

Reality Check: Forecasting Growth in the Middle East and North Africa in Times of Uncertainty

Abstract: The team received invaluable inputs from Minh Cong Nguyen and the MENA region country economists, namely Jaime

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Outlooks are available for GDP, population sizes, and inflation figures. The WEO tends to have positive bias, documented for instance by Gatti et al (2022), and may be understood as economic targets that can be met if identified risks are managed. The April WEO is put together during January -March.…”
Section: B Prediction Resultsmentioning
confidence: 99%
“…Outlooks are available for GDP, population sizes, and inflation figures. The WEO tends to have positive bias, documented for instance by Gatti et al (2022), and may be understood as economic targets that can be met if identified risks are managed. The April WEO is put together during January -March.…”
Section: B Prediction Resultsmentioning
confidence: 99%
“…However, there are increasing risks to growth in the subregion. Several countries in North Africa, such as Egypt, are net importers of oil and food and they began 2022 with high levels of debt (Gatti et al 2022). Morocco has become a net importer of food because of drought -an example of how Africa is becoming more vulnerable to climate change.…”
Section: Labour Market Trends In North Africamentioning
confidence: 99%
“…There are likely to be very different pictures for the net resource exporters and the other countries in the region. Hydrocarbon-exporting countries such as those in the GCC are predicted to benefit from higher commodity prices resulting from the conflict in Ukraine, although this highlights the region's ongoing reliance on fossil fuel production and vulnerability to global prices (Gatti et al 2022). Continuing political and economic turmoil in the region is also affecting the region's prospects; for example, the situation in Lebanon continues to limit inward investment.…”
Section: Arab Statesmentioning
confidence: 99%
“…While MENA's forecasted growth for 2022 was 5.5% (World Bank, 2022b), Gatti et al (2022) question whether the region's recovery to pre-pandemic standards of living is possible. They also note that this optimistic figure masks variations in regional growth between the more prosperous oil exporting and less wealthy oil importing countries.…”
Section: Decent Work and Economic Growthmentioning
confidence: 99%
“…Together with rising global food prices fuelled by the war in Ukraine, the region faces intensified challenges of food poverty and insecurity. So significant are such challenges that Gatti et al (2022) predict that social unrest is likely to follow. Furthermore, the region includes some of the world's most water scarce countries, which consequently threatens their access to fresh water (Sakmar et al, 2011).…”
Section: Decent Work and Economic Growthmentioning
confidence: 99%